LECTOTYPIFICATION OF VIBURNUM BECCARII (ADOXACEAE) - Ranjan, Vinay; Srivastava, S. C. (Edinburgh Journal of Botany, 2016)
A lectotype of Viburnum beccarii Gamble (Adoxaceae) is proposed with an image of the material selected.